Initial SYNTAX Score Predicts Major Adverse Cardiac Events After Primary Percutaneous Coronary Intervention. (May 2014) - Brown, Adam J.; McCormick, Liam M.; Gajendragadkar, Parag R.; Hoole, Stephen P.; West, Nick E.J.
We assessed whether interventional complexity in patients presenting with ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PPCI) predicted long-term outcome. Consecutive patients undergoing PPCI for STEMI underwent SYNTAX scoring, based on angiographic images obtained at coronary intervention. Patients were classified as SYNTAX score (SS) ≤22 (low, L), 23 to 32 [intermediate (IM)], and ≥33 (high, H). The median SS for the cohort was 19 [Interquartile range (IQR), 11.0-25.5] with median tertile scores of L 14 (IQR 9.0-18.5, n = 437), IM 26 (IQR 24.0-28.5, n = 170), and H 36 (IQR 34.5-40.5, n = 67). Two-year freedom from major adverse cardiac events (MACE) was L 88.1%, IM 78.8%, and H 68.7% ( P < .001). Multivariate analysis confirmed that increasing SS tertile was an independent predictor of MACE [IM hazard ratio (HR) 1.61, confidence interval (CI) 1.05-2.47; P = .03, H HR 1.99, CI 1.16-3.41; P = .01]. The SS, when applied to patients undergoing PPCI for STEMI, provides prognostic information.